Artes decorativas - Rivas Carmona, Jesús Francisco; Pérez Sánchez, Manuel; García Zapata, Ignacio José (EDITUM. Ediciones de la Universidad de Murcia, 2025)
This subject aims to value the significance of the so-called decorative arts, which include plots such as silverware, rejeria, textiles, furniture etc... Artistic manifestations that must be studied in depth since they had a particular significance throughoutof history linked to social elites and religious. For this, a tour of the main periods has been arranged, accompanying the most significant works of each moment as well as the great teachers who made them possible. Without forgetting what the trade, the organization of work, materials, techniques, ornamental repertoires.